2022
DOI: 10.1021/acs.estlett.2c00689
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Behavior, Speciation, and Toxicity of Microplastic-Bound Chromium in Multisolute Systems

Abstract: The unexpectedly high affinity of microplastics (MPs) for heavy metals has attracted increasing attention in recent years. However, there is a scarcity of information on the effects of coexisting constituents on plastic–metal interactions, especially in terms of metal speciation. This study aimed to explore the role of benzophenone-type UV filters on the sorption, oxidation state, and toxicity of chromium (Cr) by pristine and UV-irradiated polystyrene MPs (PSMPs). Results showed that Cr uptake by PSMPs was rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Previous research has shown that heavy metals can easily attach to MPs, a combination that can potentially harm aquatic life and, eventually, human health by contaminating the food web [126][127][128][129][130][131]. Recent studies further indicated that UV filters used, for example, in sunscreens, can increase the toxicity of chromium metal by altering the oxidation state of MP-bound metals [132]. Generally, MPs and NPs can contain numerous toxic chemicals, as recently reviewed by the United Nations Environment Programme (UNEP) [133] and by others (e.g., [81,134]).…”
Section: Bridging Gapsmentioning
confidence: 99%
“…Previous research has shown that heavy metals can easily attach to MPs, a combination that can potentially harm aquatic life and, eventually, human health by contaminating the food web [126][127][128][129][130][131]. Recent studies further indicated that UV filters used, for example, in sunscreens, can increase the toxicity of chromium metal by altering the oxidation state of MP-bound metals [132]. Generally, MPs and NPs can contain numerous toxic chemicals, as recently reviewed by the United Nations Environment Programme (UNEP) [133] and by others (e.g., [81,134]).…”
Section: Bridging Gapsmentioning
confidence: 99%
“…Though MPs are classified as emerging pollutants, they may not be hazardous per se to living beings in their native chemical compositions in a pristine microenvironment. However, their omnipresence in the environment is a matter of concern owing to their role as a vector for several hazardous agents, including heavy metals [ 63 ], rare earth elements [ 64 ], pharmaceuticals (antibiotics) [ 65 , 66 ], personal care products [ 67 , 68 ], and a variety of other emerging contaminants of concern including microbes (antibiotic-resistant bacteria, viruses, etc.) [ 69 ].…”
Section: Impacts Of Long-term Persistence Of Mps On Agroecosystemmentioning
confidence: 99%
“…The surface charges of MPs play a defining role in their interaction with heavy metals 20,[22][23] . The zeta potential (ζ) of both pristine and aged microplastics were measured in different types of background electrolytes (i.e., NaCl, CuCl2, ZnCl2) and the results are shown in Fig.…”
Section: Characterization Of Pristine and Aged Mpsmentioning
confidence: 99%
“…Microplastics have been detected in various poultry and livestock meats 12,14 , raising biotoxicity concerns beyond microplastics themselves. The binding between MPs and heavy metals under a wide range of environmentally relevant conditions has been extensively explored so far [15][16][17][18][19][20][21][22][23] . Apart from many environmental factors (e.g., pH, natural organic matter (NOM), and salinity), the inherent properties of MPs, such as small size, hydrophobicity, high surface area, and abundant surface functional groups, are believed to facilitate the adsorption of heavy metals on MPs [15][16]22 .…”
Section: Introductionmentioning
confidence: 99%